2013
DOI: 10.1073/pnas.1222895110
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral elevation of TNF-α leads to early synaptic abnormalities in the mouse somatosensory cortex in experimental autoimmune encephalomyelitis

Abstract: Sensory abnormalities such as numbness and paresthesias are often the earliest symptoms in neuroinflammatory diseases including multiple sclerosis. The increased production of various cytokines occurs in the early stages of neuroinflammation and could have detrimental effects on the central nervous system, thereby contributing to sensory and cognitive deficits. However, it remains unknown whether and when elevation of cytokines causes changes in brain structure and function under inflammatory conditions. To ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
95
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(103 citation statements)
references
References 66 publications
8
95
0
Order By: Relevance
“…P2X 7 Rs can over seconds allow larger molecules, such as Etd ϩ , to permeate, which was interpreted as a consequence of pore dilation by some workers (Yan et al, 2008;Browne et al, 2013). However, others have failed to see P2X 7 R pore dilation at the single-channel level (Riedel et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…P2X 7 Rs can over seconds allow larger molecules, such as Etd ϩ , to permeate, which was interpreted as a consequence of pore dilation by some workers (Yan et al, 2008;Browne et al, 2013). However, others have failed to see P2X 7 R pore dilation at the single-channel level (Riedel et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…In cultured hippocampal neurons, IL-1␤ enhances NMDAmediated neurotoxicity (Viviani et al, 2003) and in vivo it has been shown to be the primary mediator of vasogenic edema in ischemic injury (Basu et al, 2005). Furthermore, IL-1␤ impairs neuronal signaling in vitro by suppressing BDNF-dependent synaptic plasticity (Tong et al, 2012) and, in vivo, may decrease formation of new dendritic spines induced by microglia-derived BDNF (Parkhurst et al, 2013). In contrast to IL-1␤, IL-6 may have a dual role in CNS, preventing tissue damage and protecting different populations of neurons against excitotoxicity, or being detrimental if chronically upregulated (Spooren et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, enhanced glutamate transmission and expression of the AMPA receptor GluR1 subunit have been detected in the striatum starting from the presymptomatic phase of EAE (9). Recent evidence shows that synaptic abnormalities occur in the primary somatosensory cortex prior to T cell infiltration and microglial activation and are prevented by the peripheral administration of the soluble TNF inhibitor, XPro1595 (50). It is possible that early changes in the expression of functionally relevant neuronal genes, including those described in this article, underlie such effects.…”
Section: Discussionmentioning
confidence: 99%